Third Gesellschafts-Concert on April 9, 1820, Vienna, Austria - Gesellschaft der Musikfreunde in Wien:::Contributor:::::::::::: (Vienna; Austria, 2020)
Program for a concert organized by the Gesellschaft der Musikfreunde in Vienna on April 9, 1820. The program included Beethoven's Fifth Symphony, op. 67; a soprano aria with choir from Nicolini's Opera: Il Carlo Magno ; Gott im Frühling, a four-voice song composed by Worschischek; a Polonaise for the flute composed by Keller; and a chorus from Beethoven's Cantata Christus am Ölberge, op. 85.